2012
DOI: 10.4236/jct.2012.31012
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Chemotherapy-Induced Nausea and Vomiting with Neurokinin-1 Receptor Antagonists in Patients on AC-Based Chemotherapy—Are We There Yet?

Abstract: Chemotherapy-induced nausea and vomiting (CINV) are distressing side effects of chemotherapy. Neurokinin-1 receptor antagonists (NK1-RAs) have been incorporated in the contemporary management of CINV. However, clinical studies on NK1-RAs have shown mixed results in reducing CINV risk. Most studies focused on the use of aprepitant (APR) and casopitant (CAS) in breast cancer patients receiving AC-type (doxorubicin and cyclophosphamide) chemotherapy. In this study, we compared the study design and clinical effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Likewise, the overall proportion of younger patients with no vomiting in the palonosetron and 1-day dexamethasone group was consistent with the results observed among younger patients (<55 years) receiving aprepitant for 3 days (70 % vs. 73 %). It also should be noted that optimal nausea control remains an unmeet need in CINV research and the NK-1 receptor antagonists have not been shown to be effective in improving nausea control in patients receiving AC-containing chemotherapy [8, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the overall proportion of younger patients with no vomiting in the palonosetron and 1-day dexamethasone group was consistent with the results observed among younger patients (<55 years) receiving aprepitant for 3 days (70 % vs. 73 %). It also should be noted that optimal nausea control remains an unmeet need in CINV research and the NK-1 receptor antagonists have not been shown to be effective in improving nausea control in patients receiving AC-containing chemotherapy [8, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…With the incorporation of supportive care in contemporary cancer treatment over the past two decades, there is a drastic reduction of occurrence of severe toxicities associated with cancer treatment, as well as improvement of patients' quality of life. For example, routine prophylaxis with anti-emetics prior to chemotherapy has greatly reduced the occurrence of chemotherapy-induced nausea and vomiting [2]. Nonetheless, a number of chemotherapy-induced toxicities associated with anti-cancer treatment are still poorly managed in today's clinical practice due to the lack of research in those areas.…”
Section: Introductionmentioning
confidence: 99%